2018
DOI: 10.1002/anie.201807736
|View full text |Cite
|
Sign up to set email alerts
|

Blocking EGFR Activation with Anti‐EGF Nanobodies via Two Distinct Molecular Recognition Mechanisms

Abstract: One of the hallmarks of cancer is the overproduction of growth factors such as EGF. Despite the clinical success achieved by EGFR-targeted therapies, their long-term efficacy is compromised by the onset of drug-resistant mutations. To address this issue, a family of camelid-derived single-domain antibodies (Nbs) were generated, obtaining the first direct EGF inhibitors that prevent EGFR phosphorylation and pathway activation through this new mechanism of action. The two best Nbs were subjected to a detailed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
5
12
1
Order By: Relevance
“…We calculated the equilibrium dissociation constants (KD) at 25 °C, by either (I) plotting the level of steady-state binding for each concentration (i.e., equilibrium fitting, Figure S1); or (II) fitting the association and dissociation signals separately, as a function of time, to a given interaction model (i.e., kinetic fitting, Figure 1). For both nanobodies binding to EGF, a 1:1 Langmuir interaction model had been previously confirmed by isothermal calorimetry [19]. In agreement, a 1:1 kinetic model provided a close fit to the experimental data, as shown by the low chi-square values (χ 2 = 0.8-2.9).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…We calculated the equilibrium dissociation constants (KD) at 25 °C, by either (I) plotting the level of steady-state binding for each concentration (i.e., equilibrium fitting, Figure S1); or (II) fitting the association and dissociation signals separately, as a function of time, to a given interaction model (i.e., kinetic fitting, Figure 1). For both nanobodies binding to EGF, a 1:1 Langmuir interaction model had been previously confirmed by isothermal calorimetry [19]. In agreement, a 1:1 kinetic model provided a close fit to the experimental data, as shown by the low chi-square values (χ 2 = 0.8-2.9).…”
Section: Resultssupporting
confidence: 69%
“…Since experimental injection times in SPR are typically shorter (in our case, 120 s), more reliable KD values are measured by kinetic fitting, which is independent of steady-state levels. It should be noted that these KD values are, to some extent, lower For both nanobodies binding to EGF, a 1:1 Langmuir interaction model had been previously confirmed by isothermal calorimetry [19]. In agreement, a 1:1 kinetic model provided a close fit to the experimental data, as shown by the low chi-square values (χ 2 = 0.8-2.9).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Notably, Rossotti et al ( 57 ) reported DNA immunization-raised EGFR nanobodies with improved functionality compared to protein immunization-raised nanobodies. Nanobodies targeting EGF ( 58 ), HER2 ( 59 , 60 ), CAIX ( 61 ), death receptor 5 (DR5) ( 62 , 63 ), c-Met ( 64 , 65 ), HGF ( 66 ), AgSK1 ( 67 ), mesothelin ( 68 ), proteasome activator complex PA28 ( 69 ), ephrin receptor A4 (EphA4) ( 70 ), CEA-cell adhesion molecule-6 (CEACAM6) ( 71 ), mitochondrial translation elongation factor (TUFM) ( 72 ), protein C receptor ( 73 ), Wnt receptors (LRP5/6) ( 74 ), and CD33 ( 75 ) have also demonstrated delayed tumor growth.…”
Section: Nanobodies As a Cancer Therapeuticsmentioning
confidence: 99%
“…Hence, EGF has emerged as an alternative target for inhibiting the EGF–EGFR pathway, as demonstrated by the positive results obtained for CIMAvax‐EGF, a vaccine that induces antibodies against self EGF . In the same vein, we have recently described a family of nanobodies that bind EGF with high affinity and are able to block the EGF–EGFR interaction …”
Section: Introductionmentioning
confidence: 96%